The DEN and CCl4‐Induced Mouse Model of Fibrosis and Inflammation‐Associated Hepatocellular Carcinoma. Issue 8 (9th August 2021) - Uehara, Takeki; Pogribny, Igor P.; Rusyn, Ivan
Abstract: Human hepatocellular carcinoma (HCC) develops most often as a complication of fibrosis or cirrhosis. Although most human studies of HCC provide crucial insights into the molecular signatures of HCC, they seldom address its etiology. Mouse models provide essential tools for investigating the pathogenesis of HCC, but the majority of rodent cancer models do not feature liver fibrosis. Detailed here is a protocol for an experimental mouse model of HCC that arises in association with advanced liver fibrosis. The disease model is induced by a single injection of N ‐nitrosodiethylamine (DEN) at 2 weeks of age followed by repeated administration of carbon tetrachloride (CCl4 ) from 8 weeks of age for up to 14 consecutive weeks. A dramatic potentiation of liver tumor incidence is observed following administration of DEN and CCl4, with 100% of mice developing liver tumors at 5 months of age. This model has been employed for studying the molecular mechanisms of fibrogenesis and HCC development, as well as for cancer hazard/chemotherapy testing of drug candidates. © 2021 Wiley Periodicals LLC. Basic Protocol : The DEN and CCl4 ‐induced mouse model of fibrosis and inflammation‐associated hepatocellular carcinoma